Morphology and connectivity of parabrachial and cortical inputs to gustatory thalamus in rats. Issue 1 (7th October 2014) - Holtz, Stephen L.; Fu, Anqi; Loflin, Wyatt; Corson, James A.; Erisir, Alev
ABSTRACT The ventroposterior medialis parvocellularis (VPMpc) nucleus of the thalamus, the thalamic relay nucleus for gustatory sensation, receives primary input from the parabrachial nucleus, and projects to the insular cortex. To reveal the unique properties of the gustatory thalamus in comparison with archetypical sensory relay nuclei, this study examines the morphology of synaptic circuitry in the VPMpc, focusing on parabrachiothalamic driver input and corticothalamic feedback. Anterogradely visualized parabrachiothalamic fibers in the VPMpc bear large swellings. At electron microscope resolution, parabrachiothalamic axons are myelinated and make large boutons, forming multiple asymmetric, adherent, and perforated synapses onto large‐caliber dendrites and dendrite initial segments. Labeled boutons contain dense‐core vesicles, and they resemble a population of terminals within the VPMpc containing calcitonin gene‐related peptide. As is typical of primary inputs to other thalamic nuclei, parabrachiothalamic terminals are over five times larger than other inputs, while constituting only 2% of all synapses. Glomeruli and triadic arrangements, characteristic features of other sensory thalamic nuclei, are not encountered. As revealed by anterograde tracer injections into the insular cortex, corticothalamic projections in the VPMpc form a dense network of fine fibers bearing small boutons. Corticothalamic terminals within the VPMpc were also observed to synapse on cells that were retrogradely filled from the same injections. The results constitute an initial survey describing unique anatomical properties of the rodent gustatory thalamus. J. Comp. Neurol. 523:139–161, 2015. © 2014 Wiley Periodicals, Inc.